Improving lithium carbonate therapeutics by pegylated liposomal technology: an in vivo study. (January 2016) - Hosseini, Yasaman; Alavi, Seyed; Akbarzadeh, Azim; Heidarinasab, Amir
Abstract Bipolar disorder is a chronic mental illness which is associated with high risk of self-harm and suicide. Lithium carbonate has been suggested as a medicine to control and cure this disease. To overcome the complications related to taking lithium carbonate, nanotechnology has come to the aid of scientists. In this study, pegylated liposomal lithium carbonate nanoparticles were prepared by the reverse phase evaporation method to improve the drug's therapeutic characteristics as well as lessening its side effects. In order to synthesize pegylated liposomal lithium carbonate, phosphatidylcholine, polyethylene glycol 3350 (PEG3350), cholesterol, and lithium carbonate were mixed. The characterization of synthesized nanoparticles was determined by Zetasizer. Encapsulation and drug loading efficiency and release pattern studies were determined through spectrophotometry method. In addition, serum lithium and creatinine levels of the samples were analyzed. The mean diameter, size distribution, and zeta potential for pegylated liposomal particles containing lithium carbonate and blank pegylated liposomal were determined by Zetasizer equal to 102 nm, 0.458, and −25.1 mV; 284.2 nm, 0.427, and −28.3 mV, respectively. Drug loading and encapsulation efficiency were calculated to be 32.87 and 97.4 %, respectively. The drug release pattern demonstrated that the half-life of the nanodrug was approximately two times higher than the standard drug. The results related to the analysis of serum lithium and creatinine levels indicated that the efficiency of liposomal drug formulation was increased compared to the standard drug. Based on the findings, the nanodrug enjoyed a half-life two times higher than that of the standard drug and an efficiency level equal to it.